Problem of Creating a Professional Dictionary of Uncodified Vocabulary - MOROZOVA, O.A; YAKHINA, A.M; PESTOVA, M.S (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article considers the problem of lexicographical fixation of uncodified vocabulary in a professional dictionary. The oil sublanguage, being one of the variants of common language realization used by a limited group of its medium in conditions of official and also non-official communication, provides interaction of people employed in the oil industry. The authors conclude that the creation of a dictionary requires a special approach to the interpretation of words and the engagement of extralinguistic information, contexts and illustrative material.RESUMEN El artículo considera el problema de la fijación lexicográfica del vocabulario no codificado en un diccionario profesional. El sublenguaje del petróleo, siendo una de las variantes de la realización del lenguaje común utilizado por un grupo limitado de su medio en condiciones de comunicación oficial y también no oficial, proporciona la interacción de las personas empleadas en la industria petrolera. Los autores concluyen que la creación de un diccionario requiere un enfoque especial para la interpretación de las palabras y la participación de información extraliguista, contextos y material ilustrativo.